2014
DOI: 10.2105/ajph.2012.301122
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Outcomes in a Spanish-Language Randomized Controlled Diabetes Prevention Trial With Pregnant Latinas

Abstract: Objectives. We evaluated the effectiveness of a community-based healthy lifestyle intervention in improving dietary behaviors of pregnant Latinas from 2004 to 2006 in Detroit, Michigan. Methods. The 11-week, culturally tailored, Spanish-language Healthy Mothers on the Move (MOMs) intervention offered home visits, group classes, related activities, and social support from trained community health workers (CHWs) and peers. Dietary behaviors were measured by food frequency questionnaire. Linear mixed models esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…Setting, recruitment, intervention, data collection, outcome measurement, and analytic methods are described in detail elsewhere (Kieffer, Caldwell, et al, 2013; Kieffer et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Setting, recruitment, intervention, data collection, outcome measurement, and analytic methods are described in detail elsewhere (Kieffer, Caldwell, et al, 2013; Kieffer et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Participants in both groups received the same incentives for participation. In depth descriptions of the interventions are reported elsewhere (Kieffer et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those who consume strict vegetarian diet during pregnancy need to consult with their doctor and nutrition professionals to make sure the protein and vitamin supplementation along with vegetarian diet are provided (3,16). A randomized trial study for Latino pregnant women has shown that dietary education for improving dietary behaviors and life style changes could improve fiber consumption in this population (2). To summarize fiber is an important part of daily diet and it should be considered vital for pregnancy due to many benefits.…”
Section: Dear Editormentioning
confidence: 99%